Lercanidipine hydrochloride versus felodipine sustained-release for mild-to-moderate hypertension: a multi-center, randomized clinical trial. (26th November 2014) - Wu, Ying; Xu, Mengdan; Wang, Hao; Xu, Xin; Zhao, Shuiping; Zhang, Mei; Jin, Huigen; Yan, Jinchuan; Wang, Bangning; Gong, Jianbin; Lu, Xiang; Peng, Jianqiang; et al.
Abstract: Objective: Lercanidipine hydrochloride and felodipine sustained-release tablets comparison for the treatment of patients with mild-to-moderate primary hypertension. Research design and methods: The study was designed as a multicenter, randomized, open-label, parallel-group clinical trial. A total of 281 adult patients (18–75 years) with a mild-to-moderate primary hypertension diagnosis were randomly assigned, in a 1:1 ratio, to lercanidipine hydrochloride ( n = 139; 81 males) or felodipine sustained-release tablets ( n = 142; 87 males). Study duration was 8 weeks, including two run-in weeks and 6 weeks of treatment. Main outcome measures: The mean seated diastolic blood pressure (BP) change from baseline to 6 weeks of treatment was the primary endpoint. Main secondary efficacy parameters were: (i) mean seated systolic BP change from baseline to 6 weeks of treatment; (ii) normalization BP rate. The incidence of adverse events was also considered. Results: BP monitoring showed a significant decrease compared with baseline in diastolic BP (lercanidipine: from 96 ± 4 to 83 ± 6 mmHg, p < 0.0001; felodipine: from 96 ± 4 to 82 ± 5 mmHg, p < 0.0001). The mean systolic BP decreased, when compared with baseline values, by 18 mmHg and 19 mmHg in the lercanidipine and felodipine arm, respectively ( p < 0.0001 versus baseline for both comparisons). The normalization rates of BP were 79.5% and 87.2%, in the lercanidipine and felodipine groups, respectively (in-office monitoring; p = n.s.). In total, 73 patients experienced 103 AEs: 26.6% (37/139) in the lercanidipine group and 25.3% (36/142) in the felodipine arm ( p = n.s.). The analysis of safety showed no unexpected adverse events. Conclusions: Although the overall short follow-up of the present study should be taken into account, lercanidipine is an effective and safe treatment option for BP control in adult patients with mild-to-moderate primary hypertension.